Analysis of EM4 Probiotics Added in The Water on The Hematological Profile of Tilapia (Oreochromis niloticus) - Khansa Nur Faizah; Naufal Dzaky Fayyadhafif; Nabila Shafia; Muhammad Izzudin Azmi; Tsabitah Shabrina; Nabilah Dzakirah; Muhammad Shahruriza Rakai Mahandaru; Laily Nur Anggraini; Annisa Yuwan Ramadhani (Journal of Basic Medical Veterinary)
This journal reviews the effect of giving EM4 probiotics on the hematological profile of tilapia. This study aims to determine the effects that will arise after administering EM4 probiotics for several days on the blood of tilapia fish. This research uses experimental methods so that the results used are the results of experiments carried out by the author. The results of this study explain the blood profile of tilapia after administration of EM4 probiotics including levels of erythrocytes, leukocytes, hematocrit, hemoglobin and differential counting. There was a decrease in erythrocyte, hemoglobin, hematocrit levels, and an insignificant increase in leukocyte and hematocrit levels.